Rapid hydrogel-based phage susceptibility test for pathogenic bacteria - Patpatia, Sheetal; Schaedig, Eric; Dirks, Anna; Paasonen, Lauri; Skurnik, Mikael; Kiljunen, Saija (Frontiers in Cellular and Infection Microbiology, 2022)
Phage therapy is one alternative to cure infections caused by antibiotic resistant bacteria. Due to the narrow host range of phages, hundreds to thousands of phages are required to cover the diversity of bacterial pathogens. In personalized phage therapy, fast selection of the phages for individual patients is essential for successful therapy. The aims of this study were to set up a rapid hydrogel-based liquid phage susceptibility assay (PST) for the selection of phages for therapeutic use and to establish a “ready-to-screen” plate concept, where phages are readily stored in hydrogel as small droplets in microtiter plate wells. We first tested four commercially available hydrogels (GrowDex, Askina, Purilon, and Intrasite) for their suitability as phage matrices in PSTs with four phages, two of which infecting Escherichia coli and two Staphylococcus aureus. Of these four hydrogels, GrowDex was the best matrix for PST, as it did not inhibit bacterial growth, released phages quickly when mixed with bacterial culture, and maintained phage viability well. We then optimized the assay for both optical density and microscopy readers using GrowDex as matrix with 23 bacterial strains representing 10 different species and 23 phages possessing different morphologies and genome sizes. When the bacterial growth was monitored by microscopy reader, the PST was executed in just 3 hours, and there was no need for overnight culturing bacterial cells prior to the assay, whereas using optical density reader, bacteria had to be pre-cultured overnight, and the assay time was five hours. Finally, we evaluated the effect of three different chemical stabilizers (trehalose, hyaluronic acid, and gelatin) in a six-month stability assay with six model phages. These phages assay behaved very differently in respect to the chemical stabilizers, and there was not a single stabilizer suitable for all phages. However, when gelatin (0.01%) or hyaluronic acid (0.2 mg/ml) was used as stabilizer, all tested phages were still considered as positives in PST after a six-month storage in 1 ml volume. In “ready-to-screen” plates, the differences in phage stabilities were even more profound, varying from two to six months for the most and least stable phages, respectively.